2000
DOI: 10.1002/(sici)1097-4571(2000)51:4<313::aid-asi2>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

A spoken-access approach for chinese text and speech information retrieval

Abstract: This paper presents an efficient spoken access approach for both Chinese text and Mandarin speech information retrieval. The proposed approach is developed not only to deal with the retrieval of spoken documents, but also to improve the capability of human-computer interaction via voice input for information retrieval systems. Based on utilization of the mono-syllabic structure of the Chinese language, the proposed approach can tolerate speech recognition errors by performing speech query recognition and appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…• A vocal dialogue manager can make interaction between IR system and user more natural and effective, encouraging the use of techniques like relevance feedback and results browsing, as shown in (Chien et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• A vocal dialogue manager can make interaction between IR system and user more natural and effective, encouraging the use of techniques like relevance feedback and results browsing, as shown in (Chien et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It involves the integration of an ASR system and an IR system, and is not "simply connected by way of an input/output protocol" to an IR system (Fujii et al, 2002). This view was taken by (Chien, Wang, Bai, & Li, 2000) who built an efficient spoken-access approach for both Chinese text and Mandarin speech information retrieval, enabling users to submit spoken queries in an interactive way. The extensive experimentation reported in this paper shows that speech interaction can improve the effectiveness of information retrieval.…”
Section: Related Workmentioning
confidence: 99%
“…The approach has been adopted by Ng et al [4] By virtue of the syllabic nature of the Chinese language, the syllable seems to be a suitable sub-word unit for indexing spoken documents. Wang et al [5] and Meng et al [6] have used the syllable-based approach for indexing spoken documents in two Chinese dialects -Mandarin and Cantonese. This work extends the study reported in [6], where textual queries are used to retrieve Cantonese spoken documents.…”
Section: Proceedings Of the 5th International Workhop Information Rementioning
confidence: 99%
“…Other previous work in this area include: Mandarin spoken document retrieval by [Chien et al, 1999] and ; and the Informedia Project from CMU [Wactlar et al, 1996] which indexed audio tracks of news broadcasts with largevocabulary speech recognition and demonstrated multilingual capability in handling English and SerboCroatian.…”
Section: Introductionmentioning
confidence: 99%